Modern lighting sources and controls for energy efficient lighting and a smart control algorithm application - (:unkn) unknown (My University, 2010)
Energy is an important measure of prosperity of a nation. Energy has been the life-blood for continual progress of human civilization. Since the beginning of industrial revolution around two centuries ago, the global energy consumption has increased by leaps and bounds to accelerate the human living standard, particularly in the industrialized nations of the world. In order to assess the energy efficiency of an indoor lighting installation, a criterion for the installed electrical power is proposed which is broadly applicable and easy to use. Introducing target values for lamps and gear and taking into account some basic lighting comfort requirements, the maximum electrical power to be installed can be predicted for any kind of application. Herewith, one or more task areas with appropriate target illuminance values may be defined. The key parameter of the criterion is the analytical expression for the target utilance as a function of common lighting design parameters. Improved system is provided automatically controlling a light level of an interior space. The system includes a light sensor, motion sensors, electronic control cards, and a PC for fuzzy controller. Fuzzy Controller is determined turning on or turning off lamp groups according to information of light level and motion sensors.
Keywords: Energy efficiency; Energy saving; Fuzzy logic; Modern lighting; Sensors; Smart controls